Empowering high school students with online game literacy - S. Suyanto; Chelsy Yesicha; Belli Nasution; N. Nurjanah; Tutut Ismi Wahidar; I. Ismandianto; Winda Ersa (Universitas Muhammadiyah Malang, 2024)
The COVID-19 pandemic has led to a surge in electronic devices and smartphones in education, causing students to spend more time on screens. The mobile game market in Indonesia has grown significantly, with 3.45 billion downloads in 2022. Online games can be addictive and psychologically impactful, making it crucial to instill literacy and parental supervision to prevent addiction. In Bengkalis, Indonesia, a community service activity was conducted to foster online game literacy among students, teachers, and parents. The activities involved interactive methods and forum group discussions, using LCD media and PowerPoint. The study found that children often play games for entertainment without realizing the negative effects of excessive use, leading to smartphone addiction. Factors influencing this increase include pandemic conditions, lack of self-control, and a lack of understanding of the negative impact of excessive gadget use. The school's strict rules on bringing gadgets to school have been successful in promoting online game literacy. The program aimed to increase student knowledge and critical thinking in interacting with smartphones, fostering understanding between students and parents.